2005
DOI: 10.1002/nau.20104
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of post‐operative pain, quality of life, and physical performance during the first 6 weeks after abdominal or vaginal surgical correction of descensus uteri

Abstract: The vaginal operation to correct a descensus uteri is associated with less pain, better quality of life and better mobility during the first 6 weeks of the recovery period as compared to the abdominal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 20 publications
2
16
1
3
Order By: Relevance
“…First, we searched for randomized trials. One randomized trial was found comparing vaginal hysterectomy with an abdominal procedure and one randomized trial was found comparing vaginal hysterectomy with sacrospinous hysteropexy [6,7]. After that, prospective cohort studies, prospective, case-controlled studies, retrospective studies, and case reports were assessed.…”
Section: Sources and Search Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we searched for randomized trials. One randomized trial was found comparing vaginal hysterectomy with an abdominal procedure and one randomized trial was found comparing vaginal hysterectomy with sacrospinous hysteropexy [6,7]. After that, prospective cohort studies, prospective, case-controlled studies, retrospective studies, and case reports were assessed.…”
Section: Sources and Search Methodsmentioning
confidence: 99%
“…Therefore, 15 studies were excluded. Twenty-three studies were available in which outcome data for 1,764 women who underwent a vaginal hysterectomy for prolapse symptoms were analyzed separately, with a follow-up of between 9 and 60 months [4,5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have excluded young nulliparous females, and patients with atrophic vaginitis, vaginal infection, vaginal prolapse syndrome, or severe pelvic adhesions [13]. In two studies that compared abdominal and vaginal route surgery, no postoperative differences in vaginal sensation, ability to achieve orgasm, pregnancy rate, or rate of dyspareunia were observed [18,19]. In the present study, patient 2 had a history of hysterectomy.…”
Section: Discussionmentioning
confidence: 56%
“…At this moment, the transanal approach can only be recommended for small benign tumours or early colorectal cancers [6] One of the reasons for choosing the transvaginal route is the advantage of the elasticity of the vagina, hence allowing specimen of various sizes to be able to retrieve. Literature has shown that transvaginal extraction is most ideal and patients undergoing this technique had good post-operative outcome with clinically no significant impact on orgasm, pregnancy, dyspareunia or sexual function [7]. One of the main concerns regarding retrieval of specimen is port site or retrieval incision metastasis which was reported to be 0.9 to 3.4% by Schaeff et al [8].…”
Section: Histopathological Resultsmentioning
confidence: 99%